The Role of the State in Economic Development: Cross-Regional Experiences. - Collier, P (1998)
The paper reviews two roles of the state: the provision of security and the regulation of economic activity. I show that in both respects until recently African governments provided a poor environment, and that this discouraged private investment. Recently, in parts of Africa the objective investment environment has improved. However, Africa's history is now a liability due to the perception of high risk on the part of investors. The paper considers various 'agencies of restraint', such as the WTO, whereby African governments can improve risk perceptions through policy commitment.